SLIDE in a Leading Role: Pitch Structure in Barrie Cabena’s Sonata Festiva - Sallmen, Mark (Intersections, 2020)
Barrie Cabena’s Sonata Festiva (1971) highlights SLIDE, a chord progression familiar from the neo-Riemannian and twentieth-century Russian music-theoretic literatures. Diverse expressions of SLIDE involve chord pairs, single chords, and melodic lines in textural, tonal, and formal contexts, leading to contemplative, energetic, comedic, and triumphant effects. Aspects of pitch-class set theory help to relate SLIDE to other harmonic phenomena in the work.